Problems of implementing sustainable tourism in Poland - Niezgoda, Agnieszka (Economics and Business Review, 2004)
The paper attempts to list problems according to the concept of sustainable tourism in Poland. This concept must be discussed both in terms of the precision of definitions and the criteria to be met by specific forms of tourism that is not only economically viable, but also friendly to the environment (natural, social, and cultural). The second aim of this paper is to show a pragmatic aspect of the analysis and to identify problems facing all those in Poland who become involved in developing tourism compatible with the principles of sustainable development. The article presents sustainable tourism in the light of the Polish legislation, tasks of local governments and lists real problems of implementing sustainable tourism in Poland. (original abstract)